STRATEGI DAN KUALITAS MODEL KERUKUNAN ANTAR UMAT HINDU DAN MUSLIM DI DESA TEGALINGGAH KECAMATAN SUKASADA KABUPATEN BULELENG DALAM PERSPEKTIF PENDIDIKAN MULTI KULTUR - I Putu Gede Parmajaya (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
At present the harmony of religious life in the midst of cultural diversity is a very expensiveand increasingly difficult asset to find in the life of the nation and state in Indonesia. Themaintenance of a very pluralistic unity and unity of the Indonesian people under an inclusiveand democratic order is very much needed by the Indonesian people now and in the future. Thefact that there are still many obstacles faced by plurastic community life in establishing harmonyis due to various factors such as (1) different cultural backgrounds, (2) different customs, (3)different social backgrounds, (4) educational background. Some authors' methods and solutionsoffer in an effort to establish harmonious relations in the life of a pluralistic society such as (1)Religious and Customary Aspects of Religion, (2) awareness of all people about the importanceof harmony ... Modeling of Indigenous Leaders and Religious Leaders, (5) Interfaith Cooperation,(6) Turning on the Mutual Cooperation Culture. (7) Activating, (8) Fostering Religious People.(9) Cultivating the Sima Krama / Silaturrahmi Tradition. (10) Creating a Feeling of Love